High Origin of Ulnar Artery with Unusual Superficial Course and Abnormal Additional Branches from the Superficial Palmar Arch. - Mohandas Rao KG,; Somayaji SN,; Jyothsna P,; Jyothsna P, (Department of Surgery, UKM Medical Centre, 2012)
Though ulnar arterial variations are rare, superficial ulnar artery (SUA) is one of its commonest variations. During routine dissection in our department, we observed a unilateral case of SUA in a 70-year-old male human cadaver. It originated from the left brachial artery in the middle of the arm, 13cm above the medial epicondyle of humerus (15cm below the outer margin of first rib). From its origin, it passed downwards in the medial part of arm and forearm in a superficial plane compared to normal ulnar artery. In the hand, the SUA anastomosed with the superficial palmar branch of the radial artery, creating the superficial palmar arch. The superficial palmar arch gave additional branches to the thumb and index finger. Brachial artery divided into the radial and common interosseous arteries in the cubital fossa. The normal ulnar artery was absent. The existence of a SUA is undeniably of interest to the clinicians as well as to the anatomists. We hereby present a case of unilateral SUA along with a brief review of the literature and analysis of its clinical significance.